Analisis Faktor Yang Mempengaruhi Minat Penggunaan Sistem Informasi Akuntansi Berbasis E-commerce Pada Aplikasi Penjualan Online Dengan Menggunakan Technology Acceptance Model (TAM) (Studi Kasus Pada Pelaku UMKM di Kota Malang) - Muhammad Ulil Albab; Maslichah Maslichah; Afifudin Afifudin (Universitas Islam Malang, 2023)
This study aims to analyze the factors that influence interest in using e-commerce -based accounting information systems in online sales applications. This research is a quantitative study using primary data obtained from questionnaires and measured using a Likert scale of 1-5. The population in this study were MSME actors in Malang, the sample used slovin with a total of 99 respondents. This data uses the SPSS 25 for windows analysis technique. The results showed that Perceived ease of use, usefulness, and trust had a simultaneous effect (F) on user interest in e-commerce -based accounting information systems in online sales applications. Perceived ease of use has a positive impact on interest in using e-commerce -based accounting information systems in online sales applications. Perceived usefulness has no effect on interest in using e-commerce -based accounting information systems in online sales applications. Trust has a positive impact on interest in using e-commerce -based accounting information systems in online sales applications.Keywords: Perceived ease of use, perceived usefulness, trust interest in use